Pattern of contraction of the rotator cuff in throwers: A pilot study - Hess, S. A.; Friis, P.; Myers, D.; Richardson, C. (2000)
In the overhead athlete, rotator cuff control is essential for sporting activities. As the rotator cuff is essential for dynamic control during overhead activities, knowledge of the patterning and timing of contractions will give insight into the shoulder.